Methodology for developing and ranking the environmental development of the regions of the Republic of Belarus - Dubianok, Sniazhana A.; Kulakou, Andrei Ju.; Kononchuk, Tatyana P. (Journal of the Belarusian State University. Ecology, 2022)
The development of a rating for the environmental development of the regions of the Republic of Belarus is conditioned by the necessity of a comprehensive assessment of the environmental state of the country’s regions for the implementation of the state policy of the country in the field of sustainable development and improvement of environmental quality, as well as for increasing the efficiency of application of environmental instruments in the framework of international cooperation. Based on the analysis of international approaches to the formation and use of various environmental ratings, the concept of the rating of environmental development of the regions of Belarus at the level of administrative-territorial units (regions) and large cities (regional centers and the city of Minsk) has been developed, scientific and methodological approaches to the formation and maintenance of rating of ecological development. The ranking methodology is based on the ranking of regions according to a set of indicators grouped into three categories. For the rating of cities, 31 indicators were determined, for regions - 37 indicators, which allow for a comprehensive assessment of the current state of the components of the natural environment, the impact of the main types of economic activity on the environment and issues of the effectiveness of environmental policy at the regional level. The methodology for the rating of ecological development of regions was formalized in 2021 in the form of a technical regulatory legal act - TCP 17.02-19-2021 «Environmental Protection and Nature Management. Rating of ecological development of regions of the Republic of Belarus. Technical requirements». Scientific, methodological and practical support for the functioning of the rating of ecological development of regions will be carried out by the Ministry of Natural Resources and Environmental Protection of the Republic of Belarus. An annual update of the rating of regions and cities of the Republic of Belarus and the publication of rating data are provided. In 2021, RUE «Central Research Institute for Complex Use of Water Resources», based on the developed methodology, created the information resource «Ranking of the Environmental Development of the Regions of the Republic of Belarus», which allows automating the procedure for calculating the rating of the ecological development of the regions of Belarus, and calculated and compiled the environmental rating for 2020 year in the context of regional centers and the city of Minsk, the results of which are given in the article.